PENGARUH PENGGUNAAN ALAT PERAGA SMART TRASH BIN TERHADAP PEMAHAMAN KONSEP FISIKA MATERI TEKNOLOGI DIGITAL - Suarti, Suarti; Rauf, Masykur; Khaer, Muflihul Wahid (Program Studi Pendidikan Fisika FKIP Universitas Muslim Maros, 2024)
Pengaruh Penggunaan Alat Peraga Smart Trash Bin Terhadap Pemahaman Konsep Fisika Materi Teknologi Digital. The purpose of this study is to determine the understanding of the concept of digital technology classes taught and not taught using smart trash bin props, knowing the difference in understanding the concept of digital technology classes taught and not taught using smart trash bin props. The type of research is experimental with a posttest-only control design. The instrument used tests the understanding of concepts. Data analysis techniques use descriptive and inferential analysis. The average score of concept comprehension test results in classes taught using smart trash bin props was 80.42, with a very high category, while in classes that were not taught using smart trash bin props, it was 76.04, with a high category. The average value of the concept understanding test results taught with smart trash bin props is greater than the average value of the concept understanding test results that are not taught using smart trash bin props, so it can be concluded that the use of smart trash bin tools has a positive influence on the understanding of the concept of digital technology material. Meanwhile, the results of hypothetical testing obtained a significant value of 0.194 > 0.05, meaning that there was no significant difference in understanding of concepts between classes taught and not taught using smart trash bin props.